Captatio Benevolentiae: Potential Risks and Benefits of Flattering the Audience in a Public Political Speech. (December 2018) - Cavazza, Nicoletta; Guidetti, Margherita
Given that flattery is a form of impression management and a persuasive tool in interpersonal communication, two experiments investigated the effect of a (fictitious) political candidate praising the audience during a meeting. The flattery was addressed to the social category to which participants belong (direct flattery condition) or to another social category (observed flattery condition). The flattering message (vs. control condition) employed in the context of a public speech induced a more positive candidate evaluation on both the members of the flattered audience and the observers. The effect was not mediated by degree of message scrutiny, nor by suspicion of source ulterior motives, and it was not moderated by the level of identification with the audience. This suggests that the compliment to the audience leads the members of the flattered category to reciprocate liking and the observers to transfer the source's attitude recursively (TAR effect). Theoretical and practical implications are discussed.